1990
DOI: 10.1016/0035-9203(90)90293-n
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter (=Campylobacter) pylori in Africa

Abstract: Epigastric pain is a common complaint throughout Africa, mostly in the form of non-ulcer dyspepsia. It has recently been suggested that Helicobacter (= Campylobacter) pylori, a bacterium that colonizes the gastric mucosa and causes type B gastritis, may be the cause of this epigastric pain. This paper reports the endoscopic, histological and bacteriological findings in 57 patients presenting with epigastric pain to the University of Maiduguri teaching hospital during one year, together with a review of the Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Data from our study have confirmed the high prevalence of Helicobacter pylori in developing countries and its occurrence very early in life (7,27,28 Helicobacter pylori, suggested that waterborne spread of the infection through the contaminated municipal water supply might also be an important source of infection in developing countries (30).…”
Section: Discussionsupporting
confidence: 85%
“…Data from our study have confirmed the high prevalence of Helicobacter pylori in developing countries and its occurrence very early in life (7,27,28 Helicobacter pylori, suggested that waterborne spread of the infection through the contaminated municipal water supply might also be an important source of infection in developing countries (30).…”
Section: Discussionsupporting
confidence: 85%
“…There have been few documented cases of H. pylori from the north of the country and the majority of biopsy samples were not cultured, 2,3 although our study (from the western region) has documented work on the CLO test, culture, and gram staining. 4 In northern Nigeria, Holcombe et al 2,3 reported the prevalence of H. pylori by histology to be 87%, with culture (62% and 72.7% respectively) being positive for H. pylori. From our culture study of H. pylori, 27% of patients with gastritis and peptic ulcer in western Nigeria were positive.…”
mentioning
confidence: 99%
“…Les performances affichées du Pylorix ® étaient les suivantes : une sensibilité de 95%, une spécificité de 89,2% et une précision diagnostique de 90,7% (8).…”
Section: Patients Et Méthodesunclassified